2018
DOI: 10.1002/app.47154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment on the thermal properties of hybrid natural fiber‐reinforced composites

Abstract: The main objective of this work is to study the effect of chemical treatment on the thermal properties of hybrid natural fiber-reinforced composites (NFRCs). Different chemical treatments [i.e., alkalized and mixed (alkalized+ silanized)] were used to improve the adhesion between the natural fibers (jute, ramie, sisal, and curauá) and the polymer matrix. A differential scanning calorimetry, thermogravimetry, and a dynamic mechanical analysis were performed to study the thermal properties of hybrid NFRC. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(75 citation statements)
references
References 42 publications
3
71
0
1
Order By: Relevance
“…It is known that in a hybrid composite, failure is directly related to the strain at break of the individual reinforcing fibers [39] and it was shown in the literature that the strain at break of the glass fiber (2.5%) is lower compared to the curauá fiber (4.5%) [40], which may explain the lower strain failure of S+G composites compared to S+C. These results are in agreement with the literature [19,23,31]. Table 3 presents the data obtained from the flexural tests as a function of hybridization.…”
Section: Tensile Testsupporting
confidence: 90%
See 3 more Smart Citations
“…It is known that in a hybrid composite, failure is directly related to the strain at break of the individual reinforcing fibers [39] and it was shown in the literature that the strain at break of the glass fiber (2.5%) is lower compared to the curauá fiber (4.5%) [40], which may explain the lower strain failure of S+G composites compared to S+C. These results are in agreement with the literature [19,23,31]. Table 3 presents the data obtained from the flexural tests as a function of hybridization.…”
Section: Tensile Testsupporting
confidence: 90%
“…Figure 6 shows the composite thermal degradation as a function of hybridization. It is well known that when the material is degraded, it loses mass in the form of volatiles [31]. From Figure 6a it can be seen that the TG curves showed similar tendencies.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 65%
See 2 more Smart Citations
“…The results revealed that erosion resistance of treated samples is 20%-30% lower than untreated samples for 60°impact angle. Chemical treatment of natural fibers intended to improve the adhesion with polymer matrices were reported by numerous researchers [80][81][82][83][84][85][86][87][88]. However they had used different chemicals in their studies.…”
Section: Effect Of Fiber Treatmentmentioning
confidence: 99%